Trials and tribulations of overcoming xenograft rejection - Muhammad M Mohiuddin (Journal of the Pakistan Medical Association, 2025)
Throughout the world, there are millions of patients with terminal organ failure who are waiting for a human organ for transplantation. Over the last 20 years, due to improvement in our understanding of transplant organ rejection and progressively improved immunosuppression regimens, organ transplants have provided a significant extension of life. This success has saved many lives, but at the same time, due to increased public awareness and demand, it has created an acute shortage of organ donors.1 Not every donor organ can be used for transplantation, and multiple factors contribute to the selection of a transplantable organ based on the stringent selection criteria of these donors and the organs. Therefore, a similar tough criterion is applied to the recipients based on the urgency of the organ requirement. Continued...